Role of physical activity in addition to calcium and vitamin D supplementation in the prevention of osteoporosis in postmenopausal women: an Indian scenario - Mahesh Kumar Talele; Deo Rishi Tripathi; Amod Sharma (Al Ameen Medical College, 2014)
Background: Inadequate physical activity and dietary intake of calcium and vitamin D and other lifestyle factors contribute to the high prevalence of osteoporosis among elderly women. Objective: To find out the relation of Z score of the hip, and femoral neck using dual-energy x ray absorptiometry (DEXA) in healthy postmenopausal women with respect to duration since menopause, duration and type of physical activity and vitamin D3 level. Patients and methods: A 12 months cross sectional study. We screened elderly postmenopausal women (age >50 yrs) without any co-morbidities (subjects N=67) on OPD basis for bone mineral density (using DEXA scan of 3 sites spine, hip and neck of femur and total body). On BMD basis, the subjects were then classified into 2 groups A and B. Group A (N=23) included osteoporotic subjects (BMD T<-2.5) and Group B (N=34) included osteopenic/normal subjects (BMD T>-2.5). Detailed present and past history of diet (calcium content), physical activity levels (using duration and type of activity as per GPPAQ general practice physical activity questionnaire) and laboratory tests (serum calcium , serum phosphorus , vitamin D3 levels), we identified relative effects of each of them on bone mineral density (age matched Z scores). Bone mineral density (age matched Z scores) was measured by dual-energy x-ray absorptiometry every twelve months. Results: The correlation between physical activity, calcium, vitamin D3 levels and bone mineral density was determined by regression analysis. The strongest association was found between stair climbing and walking speed and duration of weight bearing activities and hip (femur) bone mineral densities. Approximately 95% of participants had insufficient serum 25-hydroxy vitamin D. Mean physical activity duration was 17.6 minutes/day. Conclusion: The positive association between stair climbing and walking speed and duration of weight bearing activities and hip (femur) cortical bone measures in postmenopausal women may indicate a lifestyle factor in addition to calcium and vitamin D3 supplementation that can help prevent bone loss. Given the significantly greater hours per week of weight bearing physical activity done by subjects, duration is an important determinant of the effect physical activity has on bone.